2021
DOI: 10.5455/medarh.2021.75.45-49
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Fetal Central Nervous System Anomalies Using Magnetic Resonance Imaging and Ultrasound

Abstract: Background: Most fetal abnormalities can be detected on ultrasound, the evaluation of fetal CNS abnormalities can be limited by various factors, including obesity, polyhydramnios, multiple pregnancies, and increased cranial ossification during the third trimester. Objective: This study aimed to evaluate the ability to detect fetal central nervous system (CNS) anomalies using in utero magnetic resonance imaging (iuMRI) and ultrasound (US) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…However, in some of these cases, ultrasound revealed the abnormal middle cerebral artery blood flow or small biparietal diameter and head circumference. This demonstrated that MRI could be an adjunct, which were able to detect additional lesions that were either suspected or missed on US, including destructive lesions, cortical abnormalities, corpus callosum anomalies, and posterior fossa anomalies, as previous studies have shown [ 25 27 ]. Therefore, MRI should be recommended in fetuses suspected of having CNS abnormalities on ultrasonography.…”
Section: Discussionsupporting
confidence: 53%
“…However, in some of these cases, ultrasound revealed the abnormal middle cerebral artery blood flow or small biparietal diameter and head circumference. This demonstrated that MRI could be an adjunct, which were able to detect additional lesions that were either suspected or missed on US, including destructive lesions, cortical abnormalities, corpus callosum anomalies, and posterior fossa anomalies, as previous studies have shown [ 25 27 ]. Therefore, MRI should be recommended in fetuses suspected of having CNS abnormalities on ultrasonography.…”
Section: Discussionsupporting
confidence: 53%
“…Observations such as ventriculomegaly, cortical malformations, calcifications, hepatosplenomegaly, liver signal alterations, and abnormal effusions are not exclusive to congenital CMV infection. FMR is also important for revealing cerebral abnormalities like polymicrogyria, lissencephaly, etc., which cannot be seen using ultrasound examination [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%